2006
DOI: 10.1063/1.2337996
|View full text |Cite
|
Sign up to set email alerts
|

Giant magnetoelectric effect in Metglas/polyvinylidene-fluoride laminates

Abstract: Here, the authors report thin (<100μm) and flexible magnetoelectric (ME) composites consisting of Metglas (high-μ magnetostriction) and polyvinylidene-fluoride (piezopolymer) layers laminated together. Both unimorph and three-layer configurations have been studied. The authors find that these ME laminates (i) require dc magnetic biases as low as 8Oe to (ii) induce giant ME voltage coefficients of 7.2V∕cmOe at low frequencies, and up to 310V∕cmOe under resonant drive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
156
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(158 citation statements)
references
References 22 publications
0
156
2
Order By: Relevance
“…Significantly enhanced ME effects are reported when compared with single-phase MF materials. For example, a giant ME voltage coefficient (3.1) is measured for Metglas (high-magnetic-susceptibility magnetostrictive alloy)/polyvinylidenefluoride (piezoelectric polymer) laminates, reaching 3 × 10 8 V (m · T) −1 [106], albeit only at microwave frequencies and resonant conditions. A comprehensive review of this field of research can be found in Nan et al [40].…”
Section: (I) Laminatesmentioning
confidence: 99%
“…Significantly enhanced ME effects are reported when compared with single-phase MF materials. For example, a giant ME voltage coefficient (3.1) is measured for Metglas (high-magnetic-susceptibility magnetostrictive alloy)/polyvinylidenefluoride (piezoelectric polymer) laminates, reaching 3 × 10 8 V (m · T) −1 [106], albeit only at microwave frequencies and resonant conditions. A comprehensive review of this field of research can be found in Nan et al [40].…”
Section: (I) Laminatesmentioning
confidence: 99%
“…New combinations of magnetostrictive/piezoelectric layers were needed; thus, by using high permeability magnetostrictive materials such as iron-based Metglas alloys epoxied to poly(vinylidene fluoride)(PVDF) piezoelectric polymer [7], signals as high as 7.2 V/cm.Oe at low (sub-resonant) frequency and 310 V/cm.Oe at the electromechanical resonance of the composite, were obtained. This electromechanical resonance takes place when a mechanical resonant response is excited through the magnetostrictive effect of the magnetic constituent of the laminate, or what is equivalent at its corresponding magnetoelastic resonance (MER) frequency.…”
Section: Introductionmentioning
confidence: 99%
“…2 Heterostructured materials with separate magnetic ͑or magnetostrictive͒ and ferroelectric components relax the competing demands and constraints on a single material. [3][4][5][6] Efforts have focused on magnetic materials with the largest possible magnetostriction in order to maximize the piezoelectric/magnetostrictive coupling. Magnetic flux concentration has resulted in ME coefficients as high as 21.46 V/cm Oe.…”
mentioning
confidence: 99%